Characterization of Inducible Transcription and Translation-Competent HIV-1 Using the RNAscope ISH Technology at a Single-Cell Resolution - Zhang, Wang; Svensson Akusjärvi, Sara; Sönnerborg, Anders; Neogi, Ujjwal (Frontiers in Microbiology, 2018)
Identifying the source and dynamics of persistent HIV-1 at single-cell resolution during cART is crucial for the design of strategies to eliminate the latent HIV-1 reservoir. An assay to measure latent HIV-1 that can distinguish inducible from defective proviruses with high precision is essential to evaluate the efficacy of HIV-1 cure efforts but is presently lacking. The primary aim of this study was therefore to identify transcription and translation competent latently infected cells through detection of biomolecules that are dependent on transcriptional activation of the provirus. We investigated the applicability of two commercially available assays; PrimeFlowTM RNA Assay (RNAflow) and RNAscope® ISH (RNAscope) for evaluation of the efficacy of latency reversal agents (LRAs) to reactivate the HIV-1 latent reservoir. The J-Lat cell model (clones 6.3, 9.3, and 10.6) and four LRAs was used to evaluate the sensitivity, specificity, and lower detection limit of the RNAflow and RNAscope assays for the detection and description of the translation-competent HIV-1 reservoir. We also checked for HIV-1 subtype specificity of the RNAscope assay using patient-derived subtype A1, B, C, and CRF01_AE recombinant plasmids following transfection in 293T cells and the applicability of the method in patient-derived peripheral blood mononuclear cells (PBMCs). The lower detection limit of RNAflow was 575 HIV-1 infected cells/million and 45 cells/million for RNAscope. The RNAscope probes, designed for HIV-1B, also detected other subtypes (A1, B, C, and CRF01_AE). RNAscope was applicable for the detection of HIV-1 in patient-derived PBMCs following LRA activation. In conclusion, our study showed that RNAscope can be used to quantify the number of directly observed individual cells expressing HIV-1 mRNA following LRA activation. Therefore, it can be a useful tool for characterization of translation-competent HIV-1 in latently infected cell at single-cell resolution in the fields of HIV-1 pathogenesis and viral persistence.